Decidualization of the human endometrium. (1st February 2018) - Okada, Hidetaka; Tsuzuki, Tomoko; Murata, Hiromi
Abstract: Background: Decidualization of the human endometrium, which involves a dramatic morphological and functional differentiation of human endometrial stromal cells (ESCs), is essential for the establishment of a successful pregnancy. Decidualization results from a complex interplay of transcription factors, morphogens, cytokines, cell cycle regulators, and signaling pathways. Methods: Based on a literature review, the regulation of, and the molecular mechanisms involved in, the decidualization of the endometrium are described. Main findings: Progesterone, together with proteins that are regulated by progesterone and/or cyclic adenosine monophosphate, including homeobox A10, forkhead box O1, signal transducers and activators of transcription, and heart and neural crest derivatives expressed transcript 2, forms a critical network for ESC decidualization and is a prerequisite to successful implantation. Decidualized ESCs contribute to the microenvironment at the feto–maternal interface and its direct or indirect influence on extracellular matrix remodeling, regulation of the local immune response, anti‐oxidative stress, and angiogenesis (vascular maturation). Impairment of this process is associated with a variety of pregnancy disorders, including infertility, recurrent miscarriages, and uteroplacental disorders. Conclusion: A deeper understanding of the process of decidualization is expected to provide new insights into the fields of reproductive biology and reproductive medicine. Abstract : A deeper understanding of the process of decidualization is expected to provide new insights in the fields of reproductive biology and reproductive medicine.